The genus Marattia (Marattiaceae) in Malaysia - Maideen, Haja; R, Jaman; Mohamed, Haji; I, Zulkapli; A, Latiff (Malaysian Journal of Science, 2002)
Three species of Marattia are enumerated for Malaysia. These are M. sylvatica and M. sambucina, both in Sabah and Sarawak, and M. pellucida in Sabah and a new record for Peninsular Malaysia